Validation of a nomogram to predict the risk of cancer in patients with intraductal papillary mucinous neoplasm and main duct dilatation of 10 mm or less. Issue 13 (23rd August 2019) - Jung, W; Park, T; Kim, Y; Park, H; Han, Y; He, J; Wolfgang, C L; Blair, A; Rashid, M F; Kluger, M D; Su, G H; Chabot, J A; et al.
Abstract: Background: Intraductal papillary mucinous neoplasm (IPMN) is premalignant pancreatic lesion. International guidelines offer limited predictors of individual risk. A nomogram to predict individual IPMN malignancy risk was released, with good diagnostic performance based on a large cohort of Asian patients with IPMN. The present study validated a nomogram to predict malignancy risk and invasiveness of IPMN using both Eastern and Western cohorts. Methods: Clinicopathological and radiological data from patients who underwent pancreatic resection for IPMN at four centres each in Eastern and Western countries were collected. After excluding patients with missing data for at least one malignancy predictor in the nomogram (main pancreatic duct diameter, cyst size, presence of mural nodule, serum carcinoembryonic antigen and carbohydrate antigen (CA) 19-9 levels, and age). Results: In total, data from 393 patients who fit the criteria were analysed, of whom 265 were from Eastern and 128 from Western institutions. Although mean age, sex, log value of serum CA19-9 level, tumour location, main duct diameter, cyst size and presence of mural nodule differed between the Korean/Japanese, Eastern and Western cohorts, rates of malignancy and invasive cancer did not differ significantly. Areas under the receiver operating characteristic (ROC) curve values for the nomogram predicting malignancy were 0·745 for Eastern, 0·856 for Western and 0·776 for combined cohorts; respective values for the nomogram predicting invasiveness were 0·736, 0·891 and 0·788. Conclusions: External validation of the nomogram showed good performance in predicting cancer in both Eastern and Western patients with IPMN lesions. Graphical Abstract: A nomogram to predict individual intraductal papillary mucinous neoplasm (IPMN) malignancy risk was released, with good diagnostic performance based on a cohort of 2258 Korean or Japanese patients with IPMN. This study validated a nomogram to predict malignancy risk and invasiveness of IPMN, using Eastern and Western cohorts. External validation of the nomogram showed good performance in predicting malignancy and invasive cancer in both Eastern and Western patients with IPMN. The nomogram could be applicable globally to decide customized treatment options for patients with IPMN. Useful for patients with IPMN